Pengaruh Eksternalitas Negatif dan Positif dalam Kebijakan Ekonomi Publik - Gege Laudie; Briean Sandika Arjuna; Fawwaz Ghufran; Wahjoe Pangestoeti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to analyze how negative and positive externalities influence the effectiveness of public economic policies at the regional level. Using a qualitative approach and descriptive-analytical method, the research was conducted in Tanjungpinang City through document studies, focus group discussions (FGDs), and content analysis of policy documents and scholarly literature. The findings reveal that negative externalities such as environmental pollution, traffic congestion, and industrial waste have not been optimally addressed due to weak regulation and limited policy evaluation. Conversely, positive externalities like the development of green open spaces and the provision of public education lack adequate fiscal support. Public policy interventions are predominantly disincentive-based, such as taxation and sanctions, while mechanisms to incentivize socially beneficial activities remain limited. These findings are examined through the lenses of Pigouvian Tax and Coase Theorem, emphasizing the need for evidence-based policies that internalize externalities fairly and efficiently. The study recommends improving regulatory frameworks, implementing strategic fiscal incentives, and enhancing public literacy in externality management.